The Case for Improving the Health of Ex-Prisoners. - Kinner, Stuart A; Wang, Emily A (American journal of public health, 2014)
The global prison population exceeds 10 million and continues to grow; more than 30 million people are released from custody annually. These individuals are disproportionately poor, disenfranchised, and chronically ill. There are compelling, evidence-based arguments for improving health outcomes for ex-prisoners on human rights, public health, criminal justice, and economic grounds. These arguments stand in stark contrast to current policy and practice in most settings. There is also a dearth of evidence to guide clinicians and policymakers on how best to care for this large and growing population during and after their transition from custody to community. Well-designed longitudinal studies, clinical trials, and burden of disease studies are pivotal to closing this evidence gap. (Am J Public Health. Published online ahead of print June 12, 2014: e1-e4. doi:10.2105/AJPH.2014.301883).